Cover Feature: Inherent Ethyl Acetate Selectivity in a Trianglimine Molecular Solid (Chem. Eur. J. 41/2021). Issue 41 (25th June 2021) - He, Donglin; Zhao, Chengxi; Chen, Linjiang; Little, Marc A.; Chong, Samantha Y.; Clowes, Rob; McKie, Katherine; Roper, Mark G.; Day, Graeme M.; Liu, Ming; Cooper, Andrew I.
Abstract : Guided by crystal structure prediction, a "templating" strategy was used to construct selective binding sites in a trianglimine macrocycle crystal for ethyl acetate, an important chemical raw material and solvent. The resulting molecular crystals exhibit inherently high selectivity towards ethyl acetate, and hence can separate ethyl acetate from azeotropic mixtures with ethanol. The crystals show reasonable adsorption kinetics, good reliability after multiple adsorption cycles, and hold promise for practical separation or detection applications. More information can be found in the Full Paper by G. M. Day, M. Liu, A. I. Cooper, et al. (DOI: 10.1002/chem.202101510 ).